Solving the Inverse Problem for an Ordinary Differential Equation Using Conjugation - Garcia-Mokina, G (American Institute of Mathematical Sciences, 2020)
We consider the following inverse problem for an ordinary differential equation (ODE): given a set of data points P = [(ti, xi), i = 1,., N], find an ODE x (t) = v(x) that admits a solution x(t) such that xi x(ti) as closely as possible. The key to the proposed method is to find approximations of the recursive or discrete propagation function D(x) from the given data set. Afterwards, we determine the field v(x), using the conjugate map defined by Schroder s equation and the solution of a related Julia s equation. Moreover, our approach also works for the inverse problems where one has to determine an ODE from multiple sets of data points. We also study existence, uniqueness, stability and other properties of the recovered field v(x). Finally, we present several numerical methods for the approximation of the field v(x) and provide some illustrative examples of the application of these methods. © American Institute of Mathematical Sciences.